Comments on 'The influence of rotational frontogenesis and its associated shearwise vertical motions on the development of an upper‐level front' by A. A. Lang and J. E. Martin (January A, 2010, 136: 239–252). (30th October 2012) - Schultz, David M.
Abstract: Two previous studies by Rotunno et al. (1994, J. Atmos. Sci . 51: 3373–3398) and Schultz and Doswell (1999, Q. J. R. Meteorol. Soc . 125: 2535–2562) offer conflicting views on the origin of geostrophic cold‐air advection that is sometimes present during upper‐level frontogenesis. Although Lang and Martin (2010) claim to reconcile these two studies, this comment offers four reasons why reconciliation is not possible. First, the necessary calculations to compare the tilting frontogenesis term to the horizontal frontogenesis terms are not performed. Second, the thermal‐advection tendency or isentrope‐orientation tendency in the region of the developing cold‐air advection is not calculated. Third, previous studies showing that the vertical terms in these diagnostics are likely associated with warm‐air advection, not cold‐air advection, are not disproven. This fact also may explain the predominance of relatively weak geostrophic thermal advection in climatologies of upper‐level fronts. Fourth, concerns are raised about some of the statements made in Lang and Martin (2010). These comments also fix an error in Eq. (11) in Schultz and Doswell (1999). Copyright © 2012 Royal Meteorological Society